Cultivating Disciplined Behavior in Students in Islamic Educational Institutions - Rahmadani, Mayang; Rahmi, Elvi; Helena, Helena; Fitriani, Fitriani; Yumna, Yumna (Ahlussunnah: Journal of Islamic Education, 2024)
Discipline is one of the main pillars in character development for students, particularly in the context of Islamic educational institutions that emphasize moral and spiritual values. Instilling disciplined behavior is not only aimed at establishing order in the daily lives of students in Islamic educational institutions, but also through habituation, role modeling, Islamic value-based guidance, and strengthening cooperation between teachers, parents, and the social environment. Type of research this is field research through a descriptive qualitative approach, data collection techniques were collected through observation, interviews and documentation. The results and discussion of the research are: 1) Forms of Student Discipline, student discipline at the Cahaya Di Atas Cahaya Tahfidz School in Bukittinggi City is good and increasing, such as discipline in coming to school on time, wearing complete uniforms, bringing textbooks according to the subject, and being orderly during learning. 2) School culture in improving student discipline, the culture has been implemented well and consistently, namely, implementing the school's vision and mission, the professionalism of work owned by teachers and school employees, and implementing a culture of smiling, greeting, polite, courteous, while 3) Supporting factors in improving student discipline include teacher motivation, parental cooperation, facilities and infrastructure. While the inhibiting factors are parents, education at home, and technological advances.